The fifties in America volume 2 - Super, John C., 1944-; Rasmussen, R. Kent (Pasadena, Calif. : Salem Press, 2005)
Surveys the events and people of the United States and Canada from 1950 through 1959.
Includes bibliographical references and index.
85377
Keywords: Nineteen fifties -- Encyclopedias; United States -- Civilization -- 1945- -- Encyclopedias; United States -- History -- 1945-1953 -- Encyclopedias; United States -- History -- 1953-1961 -- Encyclopedias